LiCs2La(BO3)2 and Li3K9La3(BO3)7: new mixed alkali metal lanthanum borates with three-dimensional open frameworks and short cut-off edges. Issue 10 (12th February 2018) - Ma, Ruru; Yang, Yun; Hu, Cong; Dong, Xiaoyu; Yang, Zhihua; Pan, Shilie
Abstract : LiCs2 La(BO3 )2 and Li3 K9 La3 (BO3 )7 : quaternary mixed alkali metal La-based borates with three-dimensional open frameworks and short cut-off edges. Abstract : Two new mixed alkali metal lanthanum borates, LiCs2 La(BO3 )2 and Li3 K9 La3 (BO3 )7, were synthesized through a high-temperature solution method and millimeter-sized colorless crystals were obtained. The structures of LiCs2 La(BO3 )2 and Li3 K9 La3 (BO3 )7 have an intricate three-dimensional (3D) open framework with one-dimensional (1D) infinite channels surrounded by cation polyhedra and isolated BO3 units. In particular, LiCs2 La(BO3 )2 exhibits a short cut-off edge <190 nm and a large experimental band gap of 6.20 eV, evidenced by diffuse reflection spectroscopy. Moreover, to better understand the relationship between the electronic structures and optical properties of LiCs2 La(BO3 )2, theoretical calculations using density functional theory were performed. The result indicated that LiCs2 La(BO3 )2 has a calculated birefringence of 0.036@1064 nm and the direct band gap is 4.54 eV. In addition, the effects of ion substitution on structural transition and the metal ion/boron ratio on dimensions of the B–O frameworks are also discussed in detail.